Aortic stiffness, pressure and flow pulsatility, and target organ damage - Mitchell, Gary F (Journal of applied physiology (1985), 2018)
Measures of aortic stiffness and pressure and flow pulsatility have emerged as correlates of and potential contributors to cardiovascular disease, dementia, and kidney disease. Higher aortic stiffness and greater pressure and flow pulsatility are associated with excessive pulsatile load on the heart, which increases mass and reduces global longitudinal strain of the left ventricle. Excessive stiffness and pulsatility are also associated with microvascular lesions in high-flow organs, such as the brain and kidney, suggesting that small vessels in these organs are damaged by pulsatility. This brief review will summarize evidence relating aortic stiffness to cardiovascular, brain, and kidney disease.